Healthy Lifestyle Of Students In The Educational Process By Means Of Adaptive Physical Culture - Asatillaevich, Abbasov Bakhadir (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
To develop, theoretically substantiate and experimentally verify the pedagogical conditions for the formation of a healthy lifestyle among university students using adaptive physical culture.